The Criticism of Standard and the Standard of Criticism - Gholamreza Fadaie (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Criticism is a natural and humane phenomenon, and it originates from human’s willingness to freedom. Thought is the mental moving from the base to the result and visa-versa. So, this action is subject to evaluation and criticism. In the past, all the scholars have tried to criticize, and it caused knowledge to develop and promote. Self-criticism in religious and mystic domains has had a high position. Critical Thinking is a new phenomenon which appeared after Dogmatism in the West, especially after Marxism. What is important in criticism is that the critic must be familiar with the thinking principles of the writer, and also, he should discover the thinking domains of the society where the author lives so that he can be a good critic. Frankfurt School is well-known in the field of Critical Thinking, and most of the authors in this field belonged to this school. In Critical Thinking, the most emphasis is on the internal criticism based on the objectives of the text or the institute. Presupposition is also very important. As a result, the criticism of standard and standard of criticism are two main criteria for critique.